Mechanical properties of lighweight concrete arch pan - Muhammad Aizat , Abd Ghafar (2015)
Nowadays, permanent formwork using arch pan have emerged and been applied widely rather than using conventional method, temporary formwork which is more expensive and produce a lot of wastage in term of time and workers. Recently, permanent formwork is using normal concrete which lead many problem such as the uses of scaffolding. Normal weight concrete is widely used in constructions which provide a balance of strength, workability, durability and economy for general use. However the self-weight beam is too heavy. One of the alternatives to overcome the problems is using lightweight concrete. The objective of the study is to determine the mix design that will produce concrete arch pan that can carry a minimum load of 1 kN, using foam lightweight concrete. This project study also is carried out to determine the strength of lightweight concrete arch pan. Compressive tests and flexural test were carried out for the project report. The strength of lightweight concrete was measured through the test. This research includes the design and fabrication of the arch pan by using the foam lightweight concrete. Based on the result obtained from the testing, it shows that the strength of lightweight concrete arch pan is increasing steadily with time.